Comparison of the Effects of Melatonin and Granulocyte- Colony Stimulating Factor in Cyclophosphamide Induced Cytopenic Rats - BUYUKAVCI, MUSTAFA; EMIN BUYUKOKUROGLU, MEHMET; KOC, MEHMET (Asian Journal of Chemistry, 2010)
Peripheral cytopenias including leukopenia, anemia and thrombocytopenia are important side effects of current chemotherapeutic regimens. Melatonin has been demonstrated to ameliorate some of these complications and the agent granulocyte-colony stimulating factor (G-CSF) has been widely used in treatment of chemotherapy-induced neutropenia. In this study, we compared the protective effects of melatonin and G-CSF in cyclophosphamide-induced cytopenic rats. White blood cell counts, hemoglobin levels and platelet counts were measured in six groups of animals: (i) control; (ii) cyclophosphamide (CPM) injected; (iii) melatonin injected; (iv) G-CSF injected; (v) CPM plus melatonin injected; (vi) CPM plus G-CSF injected. White blood cell counts, hemoglobin levels and platelet counts were significantly higher in cyclophosphamide plus melatonin treated rats than in cyclophosphamide alone treated animals. In the G-CSF plus cyclophosphamide treated group, only white blood cell counts were higher than the cyclophosphamide group. However, G-CSF raised the white blood cell count more than melatonin when administered following cyclophosphamide. Although melatonin has beneficial effects on the chemotherapy-induced anemia and thrombocytopenia, it is not as effective as G-CSF for preventing the leukopenia.